Estimation of Problem Drug Users in Prague in 2011 from Low-threshold Data: Modified Capture-Recapture Method, Adjusted for Clients Avoiding Any Identification (Non-Coded Clients). - Sopko, Bruno; Škařupová, Kateřina; Nečas, Vlastimil; Mravčík, Viktor (Central European Journal of Public Health, 2016)
Aim: Local prevalence estimates of problem drug use (PDU) are crucial in the process of assessment of drug situation and trends and for the planning of evidence-based policy responses. The aims of our study are twofold: to estimate the number of problem drug users (PDUs) in the Czech capital city in 2011, and to examine the usability of the capture-recapture method (CRM) modified for data from low-threshold programmes (LTPs) for drug users.Method: Six independent LTPs provided data for analysis (SANANIM, Drop-in and Progressive, each of these providing one drop-in centre and one outreach programme). After adjustment of the standard CRM formula for cases without an individual identifier, the overlaps between programmes were calculated and the size of hidden population was estimated.Results: In total, it was estimated that there were 10,754 PDUs in Prague in 2011. The current estimate is in line with estimates obtained previously using another indirect standard approach - the multiplier method.Conclusion: The modified version of CRM thus proved a reliable method for local PDU estimates.